Improvement of quality of service through wireless early regulation of unresponsive flows (WERUF) scheme - Sharina Shuhaime (2023)
This thesis reports on future transmission technology that could replace or enhance the present transmission means (wireless/wired). The objectives of this project are to study the present and future telecommunications demands and to provide a possible solution on a certain weakness are that presently exists. The thesis discusses the background of communications technology, from the First Generation, Second Generation, Enhanced Second Generation, to the Third Generation Technology. It also discusses the weaknesses that exist in the present transmission technology. Other than that, it also included research on Quality of Service classes and traffic shaping/profiling.